2013
DOI: 10.1159/000351625
|View full text |Cite
|
Sign up to set email alerts
|

Microcompartments and Protein Machines in Prokaryotes

Abstract: The prokaryotic cell was once thought of as a ‘bag of enzymes' with little or no intracellular compartmentalization. In this view, most reactions essential for life occurred as a consequence of random molecular collisions involving substrates, cofactors and cytoplasmic enzymes. Our current conception of a prokaryote is far from this view. We now consider a bacterium or an archaeon as a highly structured, nonrandom collection of functional membrane-embedded and proteinaceous molecular machines, each of which se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 181 publications
(198 reference statements)
0
26
0
1
Order By: Relevance
“…Bacteria were often considered to have little subcellular organization, but studies in recent decades have shown that prokaryotes possess intricate internal structure, including cytoskeletal elements, active transport machinery for cell division, and other specialized macromolecular structures (e.g., see Refs and ). Given that many prokaryotic cells are only a few microns in size, visualizing and understanding bacterial substructure presents a nearly insurmountable challenge for conventional fluorescence microscopy.…”
Section: Real‐world Application Of Subdiffractive Imaging and Biologimentioning
confidence: 99%
“…Bacteria were often considered to have little subcellular organization, but studies in recent decades have shown that prokaryotes possess intricate internal structure, including cytoskeletal elements, active transport machinery for cell division, and other specialized macromolecular structures (e.g., see Refs and ). Given that many prokaryotic cells are only a few microns in size, visualizing and understanding bacterial substructure presents a nearly insurmountable challenge for conventional fluorescence microscopy.…”
Section: Real‐world Application Of Subdiffractive Imaging and Biologimentioning
confidence: 99%
“…Throughout cellular biology, there are molecules that are dedicated to perform in mechanical processes and many of these activities are described as molecular motors or biological nanomachines (Saier 2013;Nelson et al 2013;Bustamante et al 2004). Just as machines perform specified work with the input of energy, there are many subcellular examples where proteins become energized and function as molecular motors to achieve a specific mechanical event.…”
Section: Molecular Motorsmentioning
confidence: 99%
“…Due to the lack of internal membranes in bacterial cells, a simplistic view was to consider that the bacterial cell was regarded as a collection of enzymes without organization. Over many decades, bacterial physiologists have dissected the microbial cell and have characterized numerous subcellular structures (Saier 2013). The genetic material, nucleoid, in bacteria appears to be dispersed throughout the cell; however, the architectural configuration and condensation of the nucleoid is highly complex and the specific chemical processes accounting for these physical rearrangements have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, however, the results from microfluidics and other studies have pointed to the radically different conclusion that individual bacteria grow in apparently the same conditions with different rates (Godin et al, 2010 ; Campos et al, 2014 ; Taheri-Araghi et al, 2015 ; Wallden et al, 2016 ). That said, there is no disagreement that major changes in the growth rate at the level of the population due to growth in nutritionally different media are accompanied by major changes in the size and composition of the cells (Schaechter et al, 1958 ).…”
Section: Introductionmentioning
confidence: 99%